Modal Analysis of Barrels for Assault Rifles - Peter LISÝ (Wojskowa Akademia Techniczna, 2012)
This paper deals with modal analysis of barrels for assault rifles. The barrels are modeled as 3-D objects. Three different barrels for analysis were used. First barrel is fully cylindrical and served as comparison to another two barrels, the design of which is quite close to the real barrels for 5.56 mm and 7.62 mm calibers. The calculation of natural frequencies and corresponding mode shapes was performed using the Finite Elements Method, using the LS-DYNA software system. Modal analysis was solved using the iterative Lanczos method. All three barrels are compared from various viewpoints. In Tables 1-3 the natural frequencies for these barrels and their corresponding mode shapes with modification in gripping and also with application muzzle compensator for two real barrels are listed. Various sizes of natural frequencies versus corresponding modes with modification in gripping and applied muzzle compensator for these barrels are shown on Figures from 4-9.
Keywords: Drgania lufy podczas strzału